Effect of ten weeks maximal eccentric and concentric resistance training on muscle force in physically active young men in isokinetic bench press - Aalto, Antti (2020)
Introduction. It has been long known that there are differences in eccentric and concentric force productions. Moreover, it has been known that eccentric and concentric resistance training effects differently on force production. This thesis is part of a larger study. The purpose of this study was to investigate how maximal eccentric and concentric resistance training effects maximal eccentric and concentric force production and how maximal eccentric training effects maximal concentric force and maximal concentric training on maximal eccentric force production.